Expectation and satisfaction of youths who participate to summer camps in Turkey - Savucu, Yüksel; Coşkuner, Zeki (My University, 2011)
Summer camps are an international voluntary youth movement. It provides positive changes in youth’s behavior. The purpose of this study was to determine the perspectives and expectations of the youths who attended as campers in Turkish summer camps and to give broad information about physical conditions of the camps and their practice methods. Between the ages of 18-24, total of 416 youths have participated. The survey has 32 questions and acquired data was analyzed with a statistical program in level of p<0.05. In conclusion, camps had the opportunity to make long lasting friendships in a friendly environment.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Youth; Summer camp; Camper; Expectation; Satisfaction